Historical national accounting and dating the Great Divergence. Issue 2 (July 2021) - Broadberry, Stephen
Abstract: By offering a particular interpretation of the new evidence on historical national accounting, Goldstone argues for a return to the Pomeranz (2000) version of the Great Divergence, beginning only after 1800. However, he fails to distinguish between two very different patterns of pre-industrial growth: (1) alternating episodes of growing and shrinking without any long-term trend in per capita income and (2) episodes of growing interspersed by per capita incomes remaining on a plateau, so that per capita GDP trends upwards over the long run. The latter dynamic pattern occurred in Britain and Holland from the mid-fourteenth century, so that Northwest Europe first edged ahead of the Yangzi delta region of China in the eighteenth century.